EFFECT OF INCORPORATION OF GERMINATED MILLET FLOUR ON IRON BIOACCESSIBILITY AND GLYCEMIC INDEX IN RTS FRUIT BEVERAGES (Applied Biological Research, 2025)
The study was carried out to formulate and evaluate the suitability of different  germinated millet flour incorporation in mango, pineapple and pomegranate  ready-to-serve (RTS) beverages. Incorporation of germinated foxtail millet or  little millet flour @ 1% in mango, pineapple and pomegranate RTS beverages  showed high dialyzable iron in germinated foxtail millet incorporated (GFMI)  mango (2.47 µg mL-1), GFMI pineapple (2.68 µg mL-1) and GMFI pomegranate  (1.65 µg mL-1) RTS beverages as compared to the germinated little millet  incorporated (GLMI) mango (1.51 µg mL-1), GLMI pineapple (1.11 µg mL-1)  and GLMI pomegranate (1.38 µg mL-1) RTS beverages and respective control  samples. Similarly, predicted glycemic index (GI) was 95.76 to 105.91, 93.86 to  103.90 and 98.62 to 110.60 in germinated foxtail millet flour, little millet flour  incorporated beverages and their control samples, respectively; even though the  GI of all the samples did not fall under low GI range. The findings suggest that  germinated millet flours can be incorporated to increase dialyzable iron content  and reduce GI of fruit beverages with further increasing the incorporation  amount in fruit beverages and validation with adequate in vivo studies.
Keywords: Bioaccessibility; bioactive compounds; flour; fruit beverage; germinated millet; glycemic index; iron